Manajemen Kurikulum Sekolah dalam Meningkatkan Mutu Pendidikan di MA Unggulan KH. A Wahab Hasbullah Jombang - Hadiana Indar Parawansa; Didin Sirojudin (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
School management can mean anything that pertains to the management of the educational process to achieve defined goals, both short, middle, and long-term. The research goal is: (1) to find out about curriculum management at KH. A Wahab Hasbullah's flagship MA school jombang (2) find out the efforts to improve the quality of education at the superior MA school KH. A Wahab Hasbullah jombang. (3) knowing the achievements in the Featured MA KH. A Wahab Hasbullah jombang. The method used in this research is descriptive qualitative. The data sources used in this study are primary sources and secondary data sources. To obtain the data needed in research, researchers used observation, interviews, and documentation. Based on the results of the study, it can be concluded that curriculum management in improving the quality of education at the Superior MA K.H. A Wahab Hasbullah. Curriculum management is a regulatory activity that includes planning, organizing, implementing, and evaluating so that the education program runs well and is in accordance with the goals set by the school. Meanwhile, to achieve quality education, it is necessary to apply curriculum management professionally. The educational institution will produce quality graduates who are able to shape their graduates to have life skills. Achievement is an achievement that has a higher value than others, called achievement, superior to others.